Cybercrime: The Phenomenon of Crime through the Internet in Indonesia - Yoga Pratama; Krisna Indra Sakti; Firmawan Setyadi; Nur Ahmad Azi Ibrahim; Ali Mukti Nur Hidayat (Proceeding International Conference Restructuring and Transforming Law, 2022)
Technology has long been thought to have two faces: good and bad. Everyone understands the importance of technological progress. However, few people are aware of the negative consequences of technology. The discussion of this article on cybercrime shows how crime has become more sophisticated as a consequence of technical instruments. Cybercrimes, which are simply defined as illegal acts committed through the use of computers or the Internet, have created new dilemmas for politicians and law enforcement officers. Carding has become a serious problem in Indonesia and must be addressed immediately. Hacking and vandalism are two more types of cyber crimes that often occur in Indonesia. Despite the fact that the estimated number of Internet users in Indonesia (4, 38 million people) less than 5% of the entire population, cybercrime should be taken seriously by everyone. Cybercrime has grown to incomprehensible proportions, posing a hazard to public safety in the flow of communications and information.